Transformative Impact of Insurance Technology Innovation on Traditional Insurance Practices - Singhal, Dhruv K (Journal of Global Economy, Business and Finance, 2025)
The insurance industry is going through a profound transformation driven by technological innovations collectively known as InsurTech. This paper examines the multifaceted impact of InsurTech on traditional insurance models, exploring how emerging technologies are reshaping product development, underwriting processes, customer engagement, and claims management. We analyze the potential of artificial intelligence, blockchain, Internet of Things (IoT), and big data analytics in creating more personalized, efficient, and customer-centric insurance solutions. The study also addresses the challenges and opportunities faced by incumbent insurers in adapting to this rapidly evolving landscape and discusses the future trajectory of the insurance industry in light of these innovations.